Aplicación móvil para gestión de información en sistemas de producción porcina - Andrade Mejía, Abel Agustín (2025)
The purpose of this project was to develop a mobile application at the UDIV of the Veterinary Medicine program at ESPAM MFL, aimed at optimizing information management in pig production systems. To this end, the agile Extreme Programming (XP) methodology was applied, noted for its adaptability and efficiency in dynamic development environments. In the planning phase, functional and non-functional requirements were identified through direct observation and document analysis, which were documented in accordance with the IEEE 830 standard, ensuring accuracy in the definition of the system. Subsequently, in the design stage, tools such as Lucidchart and Figma were used to build architectural models, use cases, and interface prototypes, which allowed for early validation of the proposal. During the coding phase, the backend was developed with Node.js and Express, the frontend with Ionic, and the database with MySQL, ensuring efficient and scalable integration. Finally, during the testing phase, validation techniques were applied to both the backend and frontend, enabling errors to be corrected early on and ensuring that end-user expectations were met. The resulting product was a mobile application with an intuitive interface that allows users to record and manage information related to pigs, vaccinations, inseminations, births, and reports, contributing to optimized decision-making and improved efficiency in pig production processes.